Pendidikan Melalui Permainan: Membangun Kreativitas dan Inovasi pada Generasi Digital - Indah Meilita Meilita; Masduki Asbari; Lelono Surya Timur (Journal of Information Systems and Management (JISMA), 2023)
freedom to explore, collaborate and create solutions. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to an oral narrative from the Bukalapak YouTube channel entitled "Education through games" explained by Aranggi Soemardjan. The results of this study show that innovative approaches to education can provide freedom in learning to prepare the generation of digital natives to face a dynamic and opportunity-filled future.